Communication of higher education institutions: Historical developments and changes over the past decade - Silke Fürst; Daniel Vogler; Isabel Sörensen; Mike S. Schäfer (Studies in Communication Sciences, 2022)
Higher education institutions (HEIs) are pivotal organizations in modern societies. Over the past decades, the higher education sector has expanded considerably in countries across the world, with many newly founded colleges and universities and rapid increases in student enrollment and research output. In addition, new public management reforms and a growing need for societal legitimation have led many HEIs to establish or enlarge their communication departments, pursue branding and reputation management, and professionalize their communication efforts across various channels. Although a growing body of literature has shed light on how HEIs engage in public relations (PR) and science communication, we know little about how their communication has developed over time and in relation to the fundamental transformations in higher education systems and the media landscape in recent years, decades, and even centuries. Most existing sketches of such historical developments have focused on one country – as is typical for histories of PR in general – and have been dedicated to the second half of the 20th century. In contrast, the early beginnings of university communication since the late 19th century and recent trends in the past decade have been little researched. This guest editorial and the contributions of this Thematic Section on Changing Communication of Higher Education Institutions address these gaps in research and together shed light on developments in different European countries, as well as in the U. S.